Extremal properties of certain class of close-to-convex functions / Wan Nor Nabila Mohd Zaini, Nurul Hazimah Zabidi and Jannatul Hidayah Mohd Azman - Mohd Zaini, Wan Nor Nabila; Zabidi, Nurul Hazimah; Mohd Azman, Jannatul Hidayah (2023)
This study is concerned with the theory of geometric functions represents a subdivision within the broad field of complex analysis. Every class of functions has extremal properties which are coefficient bound and growth theorem. This is a study of classical mathematics which involves many definitions and theorems that must be proved. In addition, it is also hard to introduce a unique class of univalent functions because some of class the function may not univalent. In this study, identifying the extremal properties presents challenges as suitable calculation methods are scarce and can prove to be intricate.